2024
DOI: 10.1161/jaha.123.031219
|View full text |Cite
|
Sign up to set email alerts
|

Deferasirox Targeting Ferroptosis Synergistically Ameliorates Myocardial Ischemia Reperfusion Injury in Conjunction With Cyclosporine A

Kosei Ishimaru,
Masataka Ikeda,
Hiroko Deguchi Miyamoto
et al.

Abstract: Background Ferroptosis, an iron‐dependent form of regulated cell death, is a major cell death mode in myocardial ischemia reperfusion (I/R) injury, along with mitochondrial permeability transition‐driven necrosis, which is inhibited by cyclosporine A (CsA). However, therapeutics targeting ferroptosis during myocardial I/R injury have not yet been developed. Hence, we aimed to investigate the therapeutic efficacy of deferasirox, an iron chelator, against hypoxia/reoxygenation‐induced ferroptosis in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 43 publications
0
0
0
Order By: Relevance
“…In recent years, she demonstrated that ferroptosis, caused by excess iron and lipid peroxides, could play an important role in the pathogenesis of cardiomyopathy and myocardial ischemia repefusion injury. 9 12 Her research group showed that doxorubicin accumulated in mitochondria by intercalating into mitochondrial DNA (mtDNA), inducing ferroptosis in an mtDNA content-dependent manner. In addition, doxorubicin disrupted heme synthesis by decreasing the abundance of 5’-aminolevulinate synthase 1 (Alas1), the rate-limiting enzyme in this process, thereby impairing iron utilization, resulting in iron overload and ferroptosis in mitochondria in cardiac myocytes.…”
mentioning
confidence: 99%
“…In recent years, she demonstrated that ferroptosis, caused by excess iron and lipid peroxides, could play an important role in the pathogenesis of cardiomyopathy and myocardial ischemia repefusion injury. 9 12 Her research group showed that doxorubicin accumulated in mitochondria by intercalating into mitochondrial DNA (mtDNA), inducing ferroptosis in an mtDNA content-dependent manner. In addition, doxorubicin disrupted heme synthesis by decreasing the abundance of 5’-aminolevulinate synthase 1 (Alas1), the rate-limiting enzyme in this process, thereby impairing iron utilization, resulting in iron overload and ferroptosis in mitochondria in cardiac myocytes.…”
mentioning
confidence: 99%